Respuesta :

Answer:

He did an error because he multiplied equation 2 wrongly.

The correct multiplication should have been:

-6x + 9y = 6        Multiply equation by 2 by 3

Step-by-step explanation:

Given the system of equations

3x-5y=4

-2x+3y=2

This is what student solved

6x - 10y = 8        Multiply equation 1 by 2

-6x + 3y = 6        Multiply equation by 2 by 3

_________

       -7y = 14

          y = -2

He did an error because he multiplied the equation 2 wrongly.

The correct multiplication should have been:

-6x + 9y = 6        Multiply equation by 2 by 3

NOW, HERE IS THE CORRECT VERSION

6x - 10y = 8        Multiply equation 1 by 2

-6x + 6y = 6        Multiply equation by 2 by 3

_________

       -4y = 14

          y = -2/7